PENGARUH EFISIENSI DIRI DAN DUKUNGAN SOSIAL TERHADAP STRES KERJA GURU - Masduki Ahmad (Akademika : Jurnal Teknologi Pendidikan, 2020)
This study aims to analyze the effects of self-efficacy and social support on work stress for civil servant teachers in Elementary School in Pondok Kelapa Village. This study uses multiple linear regression models as the main analysis tool. This study used a sample of 81 civil servant teachers at Elementary School in Pondok Kelapa Village. The research instrument was a closed questionnaire using a Likert scale and was applied via a google form. Statistical calculations in this study were carried out using SPSS version 25. To test the hypothesis, it was carried out using the t-test and the F test. From the research that has been conducted, it has in several conclusions including 1) self-efficacy has a negative and significant effect on work stress for civil servant teachers at Elementary School in Pondok Kelapa Village, with a significance value of 0.000 (α <0.005); 2) Social support has a negative and significant effect on the work stress of civil servant teachers at Elementary School in Pondok Kelapa Village, with a significance value of 0.000 (α <0.005) and 3) Self-efficacy and social support have a significant effect on work stress for civil servant teachers at Elementary School in Pondok Kelapa Village with a significance value of 0.000 (α <0.005) and a coefficient of determination of 0.597 or 59.7%.